Essence of contracts concluded for implementing corporate investment - O. Ye. Kukhariev (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on clarifying the essence of contracts in the field of corporate investment. Achieving the specified purpose is realized through the analysis of the relevant norms of the current legislation of Ukraine, court case-law and provisions of the legal doctrine, which is the objective of this article.